Evaluating The Impact of Patient Admission Flow, Block Scheduling, And Reminder System on Elective Surgery Delay Rates at Restu Ibu Hospital Balikpapan - Joan Febrian Ristanto; Bayu Wahyudi; Yuniati Lestari (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
Elective surgery delays are a major challenge in operating room management, affecting service quality, resource efficiency, and patient satisfaction. At Restu Ibu Hospital, delay rates ranged from 25–30% monthly prior to the intervention. This study evaluated the effectiveness of comprehensive OR management interventions: block scheduling, EMR-integrated digital reminders, standardized preoperative SOPs, and STARKES monitoring integration in reducing elective surgery delays. A quasi-experimental interrupted time series design with segmented regression analysis was employed. Data were collected from EMR and STARKES dashboards covering six months pre-intervention (July–December 2024) and six months post-intervention (February–July 2025). Qualitative interviews with key stakeholders illuminated the dynamics of implementation and contextual factors. Pre-intervention baseline delay rate averaged 26.8%, with a non-significant upward trend of 0.4% per month. Post-intervention, significant improvements emerged: an immediate level reduction of 13.5% (p = 0.021) and a sustained monthly decline of 1.8% (p = 0.008), reducing monthly delays to 12–15%, a 50% improvement. Secondary outcomes showed reduced first-case start delays (>20%), shorter turnover times (15–20%), and lower overtime rates (<15%). Qualitative findings identified key causes of delay, including patient tardiness, incomplete assessments, delayed OR readiness, and suboptimal coordination. The comprehensive intervention package effectively reduced elective surgery delays through integrated process standardization, scheduling reform, digital enablement, and performance monitoring. Findings demonstrate that operational excellence in resource-constrained settings derives from effective management rather than extensive infrastructure investment.